2021
DOI: 10.1021/acsnano.1c08812
|View full text |Cite
|
Sign up to set email alerts
|

Stable Doping of Single-Walled Carbon Nanotubes for Flexible Transparent Conductive Films

Abstract: Possessing excellent electronic and mechanical properties and great stability, single-walled carbon nanotubes (SWCNTs) are exceptionally attractive in fabricating flexible transparent conductive films. Doping is a key step to further enhance the conductivity of the SWCNT films and the reliable doping is highly needed. We developed a feasible strategy that uses solid acids such as phosphotungstic acid (PTA) to dope the SWCNT films stably relying on the nonvolatility of the dopants. The sheet resistance of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…Metal nanowires based TCFs possess better electrical conductivity due to the excellent electrical conductivity of metal nanowires. Therefore, metal nanowires are ideal materials to replace indium tin oxide (ITO) [10,11], carbon nanotubes [12], graphene [13,14] and conductive polymers [ [15] to fabricate TCFs. Among metal nanowires, silver nanowires (AgNW) is the most promising candidate owing to excellent conductivity, relatively low cost and convenient fabrication [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanowires based TCFs possess better electrical conductivity due to the excellent electrical conductivity of metal nanowires. Therefore, metal nanowires are ideal materials to replace indium tin oxide (ITO) [10,11], carbon nanotubes [12], graphene [13,14] and conductive polymers [ [15] to fabricate TCFs. Among metal nanowires, silver nanowires (AgNW) is the most promising candidate owing to excellent conductivity, relatively low cost and convenient fabrication [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…22 To improve the stability of the HPA-containing catalysts, some researchers used the impregnation method to load the HPA monolayer onto the surface of a support, in which the interaction between HPAs and support could maintain the stability of the catalyst. 23,24 Most of the research works on the catalytic oxidation of VOCs have been mainly focused on the removal of single pollutants, but the actual compositions of waste gases are rather complex, including CVOCs, cyclic derivatives, oxygenated derivatives, hydrocarbons, etc. Some references related to the catalytic oxidation of multicomponent VOCs containing CVOCs over different catalysts are shown in Table S1.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the stability of the commonly used HPAs decreases in the order of H 3 PW 12 O 40 (HPW) > H 4 SiW 12 O 40 (HSiW) > H 3 PMo 12 O 40 (HPMo) > H 4 SiMo 12 O 40 (HSiMo) . To improve the stability of the HPA-containing catalysts, some researchers used the impregnation method to load the HPA monolayer onto the surface of a support, in which the interaction between HPAs and support could maintain the stability of the catalyst. , …”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalates, which possess enormously versatile structures and compositions, 61,62 are considered to be ideal electron acceptors when electrostatically bonding with electron donors such as SWCNTs. [63][64][65][66][67][68][69] For example, Newton et al recently reported that polyoxometalates are spontaneously encapsulated by SWCNTs, driven by a redox reaction between the polyoxometalates and the SWCNTs. These redox materials exhibit exceptional electrochemical stability.…”
Section: Introductionmentioning
confidence: 99%